OMNIBUS LAW DI INDONESIA: PERBANDINGAN HUKUM KENEGARAAN - Alexandrio Adenfa (Fakultas Hukum Universitas Tarumanagara, 2021)
Omnibus law in Indonesia has become a critical discourse both scientifically and practically. This discourse arises from the relatively rapid drafting and ratification of the Temporary Employment Law. The formation of this law uses the method of Collective Law because it contains the substance of many laws in one law. One of the fundamental problems facing Indonesia is the lack of rules, methods and techniques for drafting general laws. On the other hand, the techniques and methods of drafting these collective laws have been practiced in different countries in order to streamline the legislative process and organize regulations. However, citizen participation is becoming one of the fundamental deficits in terms of legal compliance with the bus and coach law. The objective of this article is to review and compare the omnibus legal concept used in selected countries using the United States and Ireland as a model. This article also looks at how to shape the ideal Omnibus Law by learning from the application of the Omnibus Law in other countries that first implemented it successfully. This study concludes that the omnibus laws in the United States and Ireland help to creating hyper-regulatory symptoms that are vulnerable and hamper economic development. The above comparison must be adapted to enact